PENGARUH TREND HALAL FASHION, GAYA HIDUP, DAN BRAND IMAGE TERHADAP PREFERENSI FASHION HIJAB - Alliza Nur Shadrina, (2021)
This research aims to explain how the influence of trend halal fashion, lifestyle and brand image on hijab fashion preferences. This research uses quantitative research method. The population used in this study is all Jabodetabek college students who wear hijab. The data collection technique in this study used questionnaire method on 155 reponden. The variables used in this study consist of 2 independent variables and dependent variables. This study uses multiple linear regression data analysis techniques, validity &reliability tests, classic assumption tests, and hypothesis tests using SPSS 20 data processing programs. The results given from this study show that the three variables free of halal fashion trends, lifestyle, and brand image have a significant influence on hijab fashion preferences. Lifestyle variables have the most dominant influence on hijab fashion preferences.